GEOCAP plan for increasing the role of Indonesian Human Resources in International Geothermal Industry :Powerpoint - van der Meer, F.D. (University of Twente, 2020)
Geothermal capacity building program; National Geothermal Development Plan for Indonesia; Selected Activities in 2015; Workshop on Geothermal Reservoir Stimulation in Bandung November 2015; Outreach in Tanzania; Reports 2015; Activities in 2016; Training overview; Engaging Outreach program .